2015
DOI: 10.1152/ajpheart.00105.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosignaling in the vasculature: emerging concepts in sensing, transduction and physiological responses

Abstract: Chatterjee S, Fujiwara K, Pérez NG, Ushio-Fukai M, Fisher AB. Mechanosignaling in the vasculature: emerging concepts in sensing, transduction and physiological responses. Am J Physiol Heart Circ Physiol 308: H1451-H1462, 2015. First published April 10, 2015; doi:10.1152/ajpheart.00105.2015.-Cells are constantly exposed to mechanical forces that play a role in modulating cellular structure and function. The cardiovascular system experiences physical forces in the form of shear stress and stretch associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 100 publications
1
33
0
Order By: Relevance
“…The sprouting of blood vessels from an existing vascular network involves the spatiotemporally coordinated degradation of and, thereafter invasion into, the surrounding extracellular matrix. This requires a careful sensing and then adaptation of the cell to changing biophysical properties (Chatterjee et al, 2015;Santos-Oliveira et al, 2015). Over the past years, the vast majority of work on endothelial mechanosensing has focused on vascular remodeling processes and altered redox signaling in response to fluid shear stress (Ando and Yamamoto, 2009;Chatterjee et al, 2015;Tzima et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sprouting of blood vessels from an existing vascular network involves the spatiotemporally coordinated degradation of and, thereafter invasion into, the surrounding extracellular matrix. This requires a careful sensing and then adaptation of the cell to changing biophysical properties (Chatterjee et al, 2015;Santos-Oliveira et al, 2015). Over the past years, the vast majority of work on endothelial mechanosensing has focused on vascular remodeling processes and altered redox signaling in response to fluid shear stress (Ando and Yamamoto, 2009;Chatterjee et al, 2015;Tzima et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This requires a careful sensing and then adaptation of the cell to changing biophysical properties (Chatterjee et al, 2015;Santos-Oliveira et al, 2015). Over the past years, the vast majority of work on endothelial mechanosensing has focused on vascular remodeling processes and altered redox signaling in response to fluid shear stress (Ando and Yamamoto, 2009;Chatterjee et al, 2015;Tzima et al, 2005). However, current knowledge on the physiological role and on the regulatory behavior of mechanosensitive signaling pathways in the context of angiogenesis is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have investigated this response to reduced shear (that is, simulated ischemia) using an isolated lung preparation and isolated endothelial cells that have been flow adapted in vitro [149,150]. The loss of shear is sensed by a cell membrane complex (mechanosome) that is localized to caveolae; the mechanosome consists of platelet endothelial cell adhesion molecule (PECAM), vascular endothelial growth factor receptor 2 (VEGFR2), vascular endothelial (VE)–cadherin, and possibly other elements [149,151]. The initial response to loss of shear is the inactivation of the inwardly-rectifying K ATP channels that results in cell membrane depolarization [149,152]; these channels are normally maintained in the open configuration by shear stress.…”
Section: Physiological Roles Of Prdx6mentioning
confidence: 99%
“…To isolate the effects of only blood flow from those of O 2 , Fisher's group has established an in vivo model of pulmonary ischemia (by stopping only blood flow) in isolated and perfused rat lungs, where constant alveolar PO 2 (∼100 mmHg) was maintained by ventilation (Al-Mehdi et al, 1997;Song et al, 2001). Using this system, they identified that the cessation of blood flow was "sensed" by the endothelial cells and activated the "mechanosome" consisting of Platelet Endothelial Cell Adhesion Molecule (PECAM), VEGFR, and Vascular Endothelial (VE) cadherin (Chatterjee et al, 2014(Chatterjee et al, , 2015, to lead to the closure of K ATP channels (Olesen et al, 1988), and activation of NADPH oxidase 2 (NOX2) to generate reactive oxygen species (ROS) and nitric oxide, ultimately leading to oxidative injury (Chatterjee et al, 2008;Browning et al, 2012). Endothelial depolarization also resulted in opening Ca +2 channels with increased intracellular Ca +2 and activation of nitric oxide (NO) synthase, increase in NO, and consequent vasodilation (Chatterjee et al, 2014).…”
Section: Shear Stress In the Lung Vasculaturementioning
confidence: 99%